The complete mitochondrial genome of Crocidura rapax Allen, 1923 and its phylogenetic analyses - Zhu Liu; Lu Miao; Qiu-Ying Guo; Mei-Feng Han (Mitochondrial DNA. Part B. Resources)
This study aimed to examine the complete mitogenome sequence of Crocidura rapax Allen, 1923 using polymerase chain reaction. The mitochondrial genome of C. rapax is a circular double-stranded structure with a complete length of 17,517 bp. The mitochondrial genome of C. rapax included 13 protein-coding genes, one control region, 22 tRNA genes, two rRNA genes, and one origin of L-strand replication. This study confirmed the phylogenetic position of C. rapax in the Crocidura genus at the molecular level. The mitochondrial genome is of significant importance for elucidating the genetic background of C. rapax.